Birds of northern India - Grimmett, Richard, 1960-; Inskipp, Tim (Helm field guides., 2018)
An exploration of the birdlife of northern India and Pakistan. The plates are accompanied by text that highlights the identification, voice, habitat, altitudinal range, distribution and status of the birds. The text is on pages facing the plates, and there are distribution maps for every species.